The Physiology and Phenomenology of Action - Berthoz, Alain; Petit, Jean-Luc; Macann, Christopher (Oxford Oxford University Press, 2006)
- A highly original new work providing a important new theory for understanding the physiology of action- Brings together two authorities in the area, showing how brain scientists and philosophers can work together for the mutual benefit of their areas- Will be of interest to those in both brain science and philosophy- Though many philosophers of mind have taken an interest in the great developments in the brain sciences, the interest is seldom reciprocated by scientists, who frequently ignore the contributions philosophers have made to our understanding of the mind and brain. In a rare collaboration, a world famous brain scientist and an eminent philosopher have joined forces in an effort to understand how our brain interacts with the world. Does the brain behave as a calculator, combining sensory data before deciding how to act? Or does it behave as an emulator endowed with innate models of the world, which it corrects according to the results of experiences obtained by the senses? The two authors come from very different backgrounds - the philosopher Jean-Luc Petit belongs to the philosophical tradition of Husserlian phenomenology. Alain Berthoz has long been interested in the physiology of action (movement, posture, decision-making, perception, etc.). Drawing on cutting-edge research from the cognitive sciences, the authors have produced a highly original volume showing how phenomenology and physiology can interact to further our understanding of the brain and the mind.
Keywords: Philosophy